Pemikiran Azyumardi Azra tentang Modernisasi Pendidikan Pesantren - Kibtiyah, Meriatul (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2022)
Islamic boarding schools are original Indonesian educational institutions that have strong traditional roots in the community. In the era of modernization or the advancement of science and technology today, the pesantren education system is a question for many parties to maintain. This research was conducted to answer these doubts by raising some of Azyumardi Azra's thoughts on how to modernize pesantren and their relevance to the pesantren education system. The purpose of this study was to determine the modernization of Islamic boarding school education according to Azyumardi Azra. The use of this research is to increase the scientific treasures in the dimensions of Islamic education, to become the latest discourse in science in order to create a better education, as well as to be a solution to Islamic boarding school education in dealing with contemporary problems that are the biggest challenges for Muslim communities on the verge of and at the beginning of the millennium. new. The research that the author is doing is included in library research or library research using a qualitative descriptive approach to critical analysis. And so that the research results run well, then in data collection, the authors use the documentation method. Meanwhile, to analyze it, the author uses content analysis techniques. That is in the form of written data. Thus, the discussion in this thesis is based on a literature review of Azyumardi Azra's work. This is used to find out Azyumardi Azra's thoughts on the modernization of Islamic boarding school education. From the results of the analysis, the authors can conclude. In recent developments with the establishment of educational institutions by the Dutch colonial (modern) Islamic educational institutions (pesantren) are increasingly receding in existence and are reluctant to accept "new" things. departing from this phenomenon, Azyumardi Azra, modernizing Islamic boarding school education is carrying out changes or transformations from the traditional system to a modern system. As for the modernization of Islamic education in Indonesia, especially Islamic boarding schools, he updated the substance or content of Islamic boarding school education by incorporating general and vocational subjects, methodological updates, such as the system classical and grading, institutional reform, such as the leadership of pesantren, diversification of educational institutions, and renewal of functions, from educational functions to include socio-economic functions. Looking at the current education applied by education experts, that For Azyumardi Azra, the idea of ​​modernizing Islamic education is not only a discourse, but must also become a reality and be put into practice. ideas and reality must be built together because in this way the benefits of an idea can be felt, therefore the idea of ​​modernizing pesantren according to Azyumardi Azra is very relevant to the education being carried out at this time, namely they both want to make students study in pesantren then become more diversified and they are prepared to become prospective scientists, in addition to becoming future ulama through a special aliyah program.